Gender differences in mediation of severe occupational stress among correctional officers - Hurst, Timothy E. (American journal of criminal justice, 1997)
This study explored gender differences in how correctional officers react to severe occupational stress and addressed differences in coping processes and social support utilization. The subjects were 244 correctional officers (167 men and 77 women) employed in Kentucky medium security institutions for male offenders. The study employed a survey administered to the volunteering participants. The Ways of Coping Questionnaire was used to assess coping processes used to deal with a stressful work event, and the Maslach Burnout Inventory was used to assess severe occupational stress. Statistical analyses revealed that correctional officers experience high levels of occupational stress but did not indicate gender differences in emotional exhaustion or depersonalization. The results indicated that female officers more frequently than male officers processed stress by seeking social support, while male officers more frequently than female officers processed stress by “planful problem solving.” No differences were found in correctional officers’ relationships with oppositesex peers. The results suggested that male and female correctional officers follow traditional sex roles in coping with occupational stress, but they revealed no differences in how they are affected by occupational stress in terms of emotional exhaustion, depersonalization, and personal accomplishment.